2015
DOI: 10.1111/hiv.12257
|View full text |Cite
|
Sign up to set email alerts
|

Soluble biomarkers of immune activation and inflammation in HIV infection: impact of 2 years of effective first‐line combination antiretroviral therapy

Abstract: The rapid and sustained viral suppression produced by first-line cART reduced IL-6, IP-10 and MIG to normal levels, while sCD14, a marker of monocyte activation, remained elevated. High levels of IP-10 and MIG tended to persist in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 40 publications
6
42
0
2
Order By: Relevance
“…High plasma IP-10, IL-6 and sCD14 all consistently predict increased subsequent morbidity and mortality during ART [42, 43, 60], and high sCD163 levels have been associated with surrogate markers of neurologic and cardiovascular disease (though perhaps not cardiovascular events [61]), as well as all-cause mortality in a recent report [26, 5759, 62, 63]. As many of these biomarkers of monocyte activation may be increased by smoking and/or alcohol use, many of these associations with morbidity and mortality may be at least in part driven by behavioral risk factors and not HIV itself, though a recent report suggests that these associations persist despite adjustment for behavioral risk factors [64].…”
Section: Specific Immunologic Pathways That Predict Disease In Hiv Inmentioning
confidence: 99%
“…High plasma IP-10, IL-6 and sCD14 all consistently predict increased subsequent morbidity and mortality during ART [42, 43, 60], and high sCD163 levels have been associated with surrogate markers of neurologic and cardiovascular disease (though perhaps not cardiovascular events [61]), as well as all-cause mortality in a recent report [26, 5759, 62, 63]. As many of these biomarkers of monocyte activation may be increased by smoking and/or alcohol use, many of these associations with morbidity and mortality may be at least in part driven by behavioral risk factors and not HIV itself, though a recent report suggests that these associations persist despite adjustment for behavioral risk factors [64].…”
Section: Specific Immunologic Pathways That Predict Disease In Hiv Inmentioning
confidence: 99%
“…Epidemiological studies demonstrated that while endothelial dysfunction is reduced following HAART initiation, long term exposure to ARVd leads to the development of vasculopathy, especially with the usage of certain protease inhibitors3435. These conditions could arise from chronic induction of ER stress3637, an increase in local inflammation38, or apoptosis activation39.…”
mentioning
confidence: 99%
“…Upon ART initiation, immune activation is only partially attenuated, and not equally among all people [912]. We hypothesized that a subset of immune activation biomarkers measurable in ART initiators would not be suppressed by ART and might predict clinical failure.…”
mentioning
confidence: 99%